Pengaruh Dow Jones Industrial Average dan Indeks Hang Seng terhadap Indeks Harga Saham Gabungan pada Tahun 2021 - Shelly Midesia (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2022)
The Jakarta Composite Index (IHSG) movement is indispensable for capital market investors in their decision-making steps. This study aims at determining the effect of the Dow Jones Industrial Average and Hang Seng Index on the Jakarta Composite Index. The data used in the research are the daily close prices of IHSG, DJIA, and HSI in 2021. Regression analysis was used for data analysis, using the SPSS data processing tool. The results indicate that DJIA and HSI partially and simultaneously affect the IHSG.